Cell type-specific multi-omics analysis of cocaine use disorder in the human caudate nucleus - Zillich, Lea; Artioli, Annasara; Pohořalá, Veronika; Zillich, Eric; Stertz, Laura; Belschner, Hanna; Jabali, Ammar; Frank, Josef; Streit, Fabian; Avetyan, Diana; Völker, Maja; Müller, Svenja; et al. (Nature Communications, 2025)
Structural and functional alterations in the brain’s reward circuitry are present in cocaine use disorder (CocUD), but their molecular underpinnings remain unclear. To investigate these mechanisms, we performed single-nuclei multiome profiling on postmortem caudate nucleus tissue from six individuals with CocUD and eight controls. We profiled 30,030 nuclei, identifying 13 cell types including D1- and D2-medium spiny neurons (MSNs) and glial cells. We observed 1485 differentially regulated genes and 10,342 differentially accessible peaks, with alterations in MSNs and astrocytes related to neurotransmitter activity and synapse organization. Gene regulatory network analysis identified transcription factors including ZEB1 as exhibiting distinct CocUD-specific subclusters, activating downstream expression of ion- and calcium-channels in MSNs. Further, PDE10A emerged as a potential drug target, showing conserved effects in a rat model. This study highlights cell type-specific molecular alterations in CocUD and provides targets for further investigation, demonstrating the value of multi-omics approaches in addiction research.
Gesehen am 07.07.2025